Aluminum and Indium Complexes derived from Guanidines, Triazenes, and Amidines1. Issue 12 (4th September 2015) - Cole, Marcus L.; Davies, Aaron J.; Jones, Cameron; Junk, Peter C.; McKay, Alasdair I.; Stasch, Andreas
Abstract: The reaction of guanidines, triazenes, amidines, and lithium amidinates with trimethylamine alane ([AlH3 (NMe3 )]), lithium tetrahydridoaluminate, trimethylaluminum, aluminum trichloride, and indium trichloride is reported. Equimolar reactions utilising hindered N, N ′‐bis(2, 6‐diisopropylphenyl)guanidines afford [Al X 2 L n ] species through hydrogen elimination ( X = H) from [AlH3 (NMe3 )] ( n = 2) with HCGiso (1 ), HDGiso (2 ), or HDPiso (3 ) [CGiso = N, N ′‐bis(2, 6‐disopropylphenyl)‐ N ′′‐dicyclohexylguanidinate, DGiso = N, N ′, N ′′‐tris(2, 6‐diisopropylphenyl)guanidinate, DPiso = N, N ′‐bis(2, 6‐diisopropylphenyl)‐ P ‐2, 6‐diisopropylphenylphosphguanidinate], or through methane elimination ( X = Me) from AlMe3 [ n = 1, L = CGiso (5 )]. The analogous reactions of the triazene HTiso with LiAlH4 and AlMe3 selectively afford [AlH(Tiso)2 ] (4 ) and [AlMe2 (Tiso)] (6 ), respectively [Tiso = 1, 3‐bis(2, 6‐diisopropylphenyl)triazenide]. Reactions of N, N ′‐bis(aryl)formamidines/ates with half an equivalent of AlMe3 /AlCl3 result in [Al X L2 ] complexes [ X = Me; L = Fxy (7 ) or Fet (8 ); X = Cl; L = Fet (9 ) or L = Fiso (10 )] [Fxy = N, N ′‐bis(2, 6‐dimethylphenyl)formamidinate, Fet = N, N ′‐bis(2, 6‐diethylphenyl)formamidinate, Fiso = N, N ′‐bis(2, 6‐diisopropylphenyl)formamidinate]. Treatment of1 with one equivalent of I2 yields [AlI2 (CGiso)] (11 ). Attempts to prepare [InCl2 L] congeners of11 with L = Fxy and Fet led to the isolation of prodigious quantities of [InCl3 (HFxy)2 ] (12 ) and [InCl2 (Fet)(HFet)] (13 ) due to adventitious water. The X‐ray crystal structures of1 –13 are reported. Abstract :